Performance of a diesel engine using different biodiesel blends and injection configurations - Sala,José A. (2023)
ABSTRACT Diesel cycle engines are widely used in a wide range of agricultural activities. Recently, with the increasing use of biodiesel mixed with petroleum diesel and the introduction of pollutant emission regulations for agricultural and road machinery, there has been a growing migration from mechanical to electronic fuel injection systems. In this experiment, the primary aim was to verify the behavior of a diesel engine, electronically managed, with controlled variation of the fuel feeding system parameters (injection time and volume injected). A four-cylinder agricultural tractor with a turbocharged engine and a common rail electronic fuel injection system was used. Tests with diesel B10 and blends of 20 and 30% biodiesel were carried out, all with 10 ppm of sulfur and the injection system electronically reprogrammed. The tests were performed under full engine load from 1,300 to 2,000 rpm. The torque, power and fuel consumption were evaluated. Advancing the injection point increased the power and decreased the specific fuel consumption for all fuels. The greater amount of injected fuel provided average power gain of up to 14.96% and average torque gain of 15.50%.